Pneumonic and non-pneumonic exacerbations in bronchiectasis: Clinical and microbiological differences. Issue 2 (August 2018) - Polverino, Eva; Rosales-Mayor, Edmundo; Benegas, Mariana; Menendez, Rosario; Alcaraz-Serrano, Victoria; Ansotegui, Emilio; Montull, Beatriz; Girón, Rosa María; Cisneros, Carolina; Vendrell, Montserrat; Muñoz, Gerard; Marcos, María Angeles; et al.
Highlights: We studied bronchiectasis (BE) patients who presented at hospital with pneumonic (CAP) or non-pneumonic (NOCAP) exacerbations. The clinical presentation was similar in patients with CAP or NOCAP exacerbations, except that CAP patients had higher temperature and higher creatinine, glucose, leukocytes and C-reactive protein (C-RP) levels. A cut-off value of C-RP ≥ 8.38 mg/dL can predict CAP in bronchiectasis. S. pneumoniae was the main cause of CAP while P. aeruginosa was the main cause of NOCAP. It is important to distinguish between CAP and NOCAP in bronchiectasis since the antibiotic coverage must be different. We suggest a complete microbiological investigation. Summary: Objectives: Despite the clinical relevance of exacerbations in bronchiectasis (BE), little is known about the microbiology and outcomes of pneumonic (CAP) vs. non-pneumonic (NOCAP) exacerbations. Methods: This study compares clinical and microbiological characteristics of CAP vs. NOCAP in adults with BE. We performed a multicenter prospective observational study of consecutive cases of NOCAP and CAP from four Spanish hospitals (2011-2015). Results: We recruited 144 patients, 47 of them CAP (33%) cases. CAP patients were older, with a larger representation of males, more comorbidities, higher arterial hypertension and COPD but less chronic bronchial infection and previous history of exacerbations. Clinical presentation was similar, excepting creatinine, C-reactive protein (C-RP), glucose and leukocytes which were higher in CAP. C-RP of 8.38 mg/dL showed a significant predictive discrimination for CAP. Streptococcus pneumoniae and Pseudomonas aeruginosa were the first causes of CAP and NOCAP, respectively. The rate of microbiological concordance with previous chronic bronchial infection was variable. Main clinical outcomes (mortality, length of stay, etc.) were similar in the two groups. Chronic bronchial infection and history of frequent exacerbations (≥ 2/year) were associated with a reduced risk of CAP. Conclusions: CAP and NOCAP in BE had similar clinical presentation with the exception of fever, leukocytosis, and C-RP. Microbiology also differed. A cut-off value of C-RP ≥ 8.38 mg/dL can predict CAP in bronchiectasis.